Expansion of Notary's Authority Extention in Organizing and Developing Cooperatives: Problems of Ambiguity of Norms and Their Solutions - I Gede Abdhi Satrya Mahardika (Universitas Bali Dwipa, 2025)
This research is based on the problem of vague norm regarding the expansion of notary authority in the administration and development of cooperatives. Research was conducted to find a solution to the problem by using relevant legal theories. This research is normative legal research that uses a statutory a conceptual approach. The results of the research showing that the expansion of notary authority in organizing and developing cooperatives leaves the problem of vague norm. The problem occurs because there were articles whose normative construction is not clear enough, resulting in vague norms. Furthermore, the problem of vague norms can be solved by using several relevant legal theories. These legal theories are the theory of legal certainty, the theory of authority, and the theory of obedience.